Human Primary Epithelial Cell Models: Promising Tools in the Era of Cystic Fibrosis Personalized Medicine - Awatade, Nikhil T.; Wong, Sharon L.; Hewson, Chris K.; Fawcett, Laura K.; Kicic, Anthony; Jaffe, Adam; Waters, Shafagh A. (Frontiers in Pharmacology, 2018)
Cystic fibrosis (CF) is an inherited disorder where individual disease aetiology and response to therapeutic intervention is impacted by CF transmembrane regulator (CFTR) mutations and other genetic modifiers. CFTR regulates multiple mechanisms in diverse range of epithelial tissues. In this Review, we consolidate the latest updates in the development of primary epithelial cellular model systems relevant for CF. We discuss conventional two-dimensional (2-D) airway epithelial cell cultures, the backbone of in vitro cellular models to date, as well as improved expansion protocols to overcome finite supply of the cellular source. We highlight range of strategies for establishment of the three dimensional (3-D) airway and intestinal organoid models and evaluate the limitations and potential improvements in each system, focusing on their application in CF. The in vitro CFTR functional assays in patient-derived organoids allow for preclinical pharmacotherapy screening to identify responsive patients. It is likely that organoids will be an invaluable preclinical tool to unravel disease mechanisms, design novel treatments and enable clinicians to provide personalized management for patients with CF.